Penggunaan Model Pembelajaran Problem Based Learning dalam Peningkatan Keaktifan Belajar Siswa pada Mata Pelajaran Pendidikan Agama Katolik dan Budi Pekerti Kelas IX SMP Budi Murni 2 Medan Analisis Website Sistem Informasi Akademik (Simak) - Simbolon, Erikson; Br Ginting, Jenny Anjelina; Tibo, Paulinus (Universitas Batanghari Jambi, 2024)
The research aims to investigate the use of the Problem Based Learning (PBL) model in ninth-grade students at SMP Budi Murni 2 Medan to assess the improvement in students' learning activeness in the subject of Catholic Religious Education. This study utilizes a qualitative approach and employs three data collection techniques: observation, interviews, and documentation. The data processing technique involves the use of source triangulation analysis and techniques. The targets of this research are ten ninth-grade students from SMP Budi Murni 2 Medan, one PAK (Pendidikan Agama Katolik) teacher, one Deputy Principal, and two peer teachers. The research findings include the following: First, the implementation of the learning model by the teacher in ninth-grade at SMP Budi Murni 2 Medan follows the five steps in the Catholic Religious Education subject at the school. Second, the evidence indicates an improvement in the learning activeness of ninth-grade students when the teacher applies the Problem Based Learning model in the subject of Catholic Religious Education.